Technologies for Professional Training Development of Future Builders-Engineers on the Basis of Innovation Approach - o‘g‘li, Turg‘Unov Muxriddin Sotvoldi (Antis Publisher, 2024)
The interest of civil engineering students can be further increased by creating a model of the elements of the assembled structures and analyzing the assembly processes during the course design work in the science of building construction technologies. The modeled constructions have a much simpler appearance, closer to reality, it is easy to implement, and students themselves try to do it practically with the help of models. Describes the extent to which the developed model is suitable for the environment in which it should work in the future.